A territorial analysis of the Gender Differences in Romanian Permanent Emigration - Babucea, Ana-Gabriela; Răbonțu, Cecilia-Irina; Bălăcescu, Aniela (Industrija, 2017)
Romanian emigration is a mass phenomenon, which caused intense debate and numerous studies and research, both in terms of causes, and especially its effects, demonstrating a complex and multidimensional nature. Social and economic problems caused by emigration both for the country of origin and for the destination country become acuter. The statistical data shows that the number of women who leave Romania is higher than men, and research studies revealing the feminization of Romanian emigration, with more profound implication if we considered Romanian demographic trend. The aim of the study is to evaluate the assumption that the Romanian permanent emigration is distributed differently by gender and that there is a different concentration at the territorial level, considered the emigrants’ departure place. The dataset used regard the distribution of the number of permanent migrants, women, and men, by their origin place both development region and county, for the period 1990-2014.